2011
DOI: 10.1371/journal.pone.0024066
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Peptide Profiles in Plasma Membrane and Membrane Rafts of PUFA Supplemented RAW264.7 Macrophages

Abstract: The eukaryotic cell membrane possesses numerous complex functions, which are essential for life. At this, the composition and the structure of the lipid bilayer are of particular importance. Polyunsaturated fatty acids may modulate the physical properties of biological membranes via alteration of membrane lipid composition affecting numerous physiological processes, e.g. in the immune system. In this systematic study we present fatty acid and peptide profiles of cell membrane and membrane rafts of murine macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 52 publications
6
43
0
Order By: Relevance
“…In this paper, the significant decrease in linoleic acid might be closely related to male fertility in PFOA-exposed mice. Changes in PUFA composition affects cell membrane fluidity, harms membrane function, and may even lead to death and apoptosis within cells (Labbe et al, 1995;Garcia et al, 2011;Schumann et al, 2011). PUFAs in membranes are prone to lipid peroxidation damage based on the degree of polyunsaturation of the fatty acids, among which DHA is the most susceptible to lipid peroxidation as it has six double bonds (Hulbert et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the significant decrease in linoleic acid might be closely related to male fertility in PFOA-exposed mice. Changes in PUFA composition affects cell membrane fluidity, harms membrane function, and may even lead to death and apoptosis within cells (Labbe et al, 1995;Garcia et al, 2011;Schumann et al, 2011). PUFAs in membranes are prone to lipid peroxidation damage based on the degree of polyunsaturation of the fatty acids, among which DHA is the most susceptible to lipid peroxidation as it has six double bonds (Hulbert et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…3 c) was different due to the radical reactions associated with carbon double bond. In the C 1s spectra of oleic and linoleic acid a shoulder related to C-O bond [59,61] As stearic, oleic and linoleic acids are the main components of bacterial membranes [58,67] it can be suggested that the chemical changes that were observed in those fatty acids upon exposure to photoactivated nano-TiO 2 thin film were also taking place in E. coli cells. Thus, it is reasonable to suggest that already after short-time exposure of E. coli to photo-activated nano-TiO 2 , unsaturated fatty acids first change their chemical composition followed by mineralization whereas saturated fatty acids just mineralize.…”
Section: Photoinduced Antibacterial Activity Of Nano-tio 2 Thin Filmsmentioning
confidence: 99%
“…N-3 PUFAs also consistently have been implicated in lipid raft regulation of immunomodulation (Ariel et al, 2005; Basiouni et al, 2012; Baumer et al, 2010; Bonilla et al, 2010; Chentouf et al, 2010; De Smedt-Peyrusse et al, 2008; Diaz et al, 2002; Geyeregger et al, 2005; Gurzell et al, 2013; Hou et al, 2012; Kim et al, 2008b; Li et al, 2005; Li et al, 2007; Li et al, 2008; Murakami et al, 2012; Ruth et al, 2009; Schumann et al, 2011; Teague et al, 2013; Van Laethem and Leo, 2002; Webb et al, 2000; Wong et al, 2009a; Zeyda et al, 2002), including a direct influence on lipid raft modulation of Toll-like receptor 4, a factor governing induction of genes that regulate inflammatory responsiveness (Wong et al, 2009a). …”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%